The potential implications of autonomous vehicles for active transport. (December 2019) - Booth, Leon; Norman, Richard; Pettigrew, Simone
Abstract: Introduction: Active transport (e.g., walking, cycling, and public transport) is associated with numerous health benefits and is the most environmentally sustainable means of personal transport. The introduction of autonomous vehicles (AVs) is expected to result in wide-scale changes to active transport behaviors. Assessing the likely extent of these changes is important to inform strategies designed to minimize disruptions to active transport resulting from AVs. Methods: An online survey was administered to a national sample of 1624 Australians of driving age (16 years and older). Respondents reported their current levels of engagement in walking, cycling, and/or public transport, and how likely they would be to use an AV instead of these activities. Regression models were used to explore how demographic, psychological, and various transport-related factors were associated with the likelihood of substituting AVs for each mode of active transport. Results: Substantial minorities of respondents indicated that they would be likely to use AVs instead of walking (18%), cycling (32%), and public transport (48%). The examined factors accounted for significant amounts of variance in each regression model. One factor was significant in all three models: a more favorable general attitude to AVs was associated with a greater likelihood of replacing walking, cycling, and public transport with AV use. Conclusions: Overall, the results suggest that AVs could substantially reduce participation in active transport, with corresponding disbenefits for individuals and society. Policies need to be implemented immediately to promote the use of active transport and minimize the migration from active transport to AVs. Highlights: Active transport is important for individual and societal well-being. A substantial number of people may replace active transport with autonomous vehicles. Positive attitudes to autonomous vehicles increased substitution intentions. Strategies are needed to promote active transport over other forms of transport.